Loan Sales and the Cost of Bank Capital - Pennacchi, George (Journal of Finance, 1988)
This paper considers a model where banks may improve the returns on loans by monitoring borrowers. Bank regulation, together with competitive deposit and equity financing, can give banks an incentive to sell loans, but the extent of their loan selling is limited by a moral-hazard problem. A solution is given for the optimal design of the bank-loan buyer contract that alleviates this moral-hazard problem. An explanation is also given as to why some banks might buy loans and why loan sales volume has recently increased.